Design and modelling of a three-phase grid-connected photovoltaic for low voltage network using PSCAD software - Hairi, Mohd Hendra; Mohd Zambri, Mohd Khairi; Hanaffi, Farhan; Ab Rahman, Azhan; Kamarudin, Muhammad Nizam (Penerbit Universiti, UTeM, 2019)
This paper presents the design and modeling of a Three-Phase Grid-Connected Photovoltaic (PV) generator module in PSCAD/EMTDC. The model is useful for simulation studies of grid interface applications. The validity of the PV model developed has been verified using a set of case studies. The output power from the PV module can be controlled through the PI controller. All the simulation study has been done in the PSCAD/EMTDC simulation software. The simulation results show that the simulation models are robust with acceptable performance in terms of power sharing between the load and the grid.